Evaluation of Nutritional Status in a Teaching Hospital Neonatal Intensive Care Unit - Mohammadreza Rafati; Maryam Nakhshab; Vagihe Ghaffari; Mohammadreza Mahdavi; Mustafa Sharifi (Mashhad University of Medical Sciences, 2015)
Background:Extrauterine growth restriction remains a common and serious problem in newborns especially who are small, immature, and critically ill. Very low birth weight infants (VLBW) had 97% and 40% growth failure at 36 weeks and 18-22 months post-conceptual age respectively. The postnatal development of premature infants is critically dependent on an adequate nutritional intake that mimics a similar gestational stage. Deficient protein or amino acid administration over an extended period may cause significant growth delay or morbidity in VLBW infants. The purpose of this study was to evaluate current nutritional status in the neonatal intensive care unit in a teaching hospital.Methods:During this prospective observational study, the nutritional status of 100 consecutive critically ill neonates were evaluated by anthropometric and biochemical parameters in a tertiary neonatal intensive care unit. Their demographic characteristics (weight, height and head circumference), energy source (dextrose and lipid) and protein were recorded in the first, 5th, 10th, 15th and 20th days of admission and blood samples were obtained to measure serum albumin and prealbumin. The amount of calorie and protein were calculated for all of preterm and term neonates and compared to standard means separately. Results: The calorie and amino acids did not meet in the majority of the preterm and term neonates and mean daily parenteral calorie intake was 30% or lower than daily requirements based on neonates' weight. Mortality rate was significantly higher in neonates with lower serum albumin and severity of malnutrition but not with serum prealbumin concentration. Conclusion: Infants were studied did not receive their whole of daily calorie and protein requirements and it is recommended early and enough administration of calorie source (dextrose, lipids) and amino acids. Prealbumin was a more benefit biochemical parameter than albumin to evaluate short term nutrition especially in critically ill patients.